Analisis Perbandingan Efektifitas Iklan Cetak dan Iklan Digital dalam Meningkatkan Penjualan Produk di Toko Istana Sarung Wonorejo - Wahidatun Nikmah; Aprilia Wulandari; Nufaila Putri; Achmad Candra Irawan; Abdurrohim Abdurrohim; Miftahul Huda (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to compare the effectiveness of print and digital advertisements in increasing sarong sales at Toko Istana Sarung Wonorejo. Using a quantitative approach, sales data from the first three months of 2025 were analyzed based on digital advertisements (social media), print advertisements (brochures and banners), and word-of-mouth promotions. The results show that digital advertising had the greatest impact on sales growth (approximately 50%), followed by word-of-mouth promotion (5–10%), and print advertising (around 15%). These findings highlight the importance of a multichannel marketing strategy tailored to consumer characteristics.